2018
DOI: 10.1158/1538-7445.am2018-ct072
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT072: First in human (FIH) dose escalation studies of intravenous administration of VSV-IFNβ-NIS (Voyager-V1™) in Stage IV or recurrent endometrial cancer

Abstract: Introduction. VSV-IFNβ-NIS is an oncolytic vesicular stomatitis virus (VSV; Rhabdovirus family) with rapid replication kinetics and potent antitumor activity. VSV-IFNβ-NIS encodes the human interferon beta (IFNβ) gene as a STING agonist and the human sodium iodide symporter (NIS) as a reporter gene for tracking the pharmacokinetics (PK) of virus replication in infected tumors. VSV replicates selectively in cancer cells and has promising preclinical antitumor activity across a broad spectrum of cancer types. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Immuno-phenotyping of blood cells on days 3, 8, 15 and 29 after infusion showed that CD8 + T cells are activated (PD1 expression level was increased). Analysis of biopsies on days 29 and 3 months after infusion showed an increase in the number of TILs [ 172 ]. As for the Phase I clinical trial (NCT03017820) of intravenous administration of VSV-IFNβ-NIS for patients with relapsed refractory multiple myeloma, acute myeloid leukemia and T-cell lymphoma the published preliminary report showed that VSV-IFNβ-NIS is well tolerated at dose level 1.7 × 10 11 TCID50.…”
Section: Oncolytic Viruses In Clinical Trialsmentioning
confidence: 99%
“…Immuno-phenotyping of blood cells on days 3, 8, 15 and 29 after infusion showed that CD8 + T cells are activated (PD1 expression level was increased). Analysis of biopsies on days 29 and 3 months after infusion showed an increase in the number of TILs [ 172 ]. As for the Phase I clinical trial (NCT03017820) of intravenous administration of VSV-IFNβ-NIS for patients with relapsed refractory multiple myeloma, acute myeloid leukemia and T-cell lymphoma the published preliminary report showed that VSV-IFNβ-NIS is well tolerated at dose level 1.7 × 10 11 TCID50.…”
Section: Oncolytic Viruses In Clinical Trialsmentioning
confidence: 99%